5-Lipoxygenase DNA Methylation and mRNA Content in the Brain and Heart of Young and Old Mice. (22nd November 2009) - Dzitoyeva, Svetlana; Imbesi, Marta; Ng, Louisa W.; Manev, Hari
Abstract : The expression of 5-lipoxygenase (5-LOX) is affected by aging and regulated by epigenetic mechanisms including DNA methylation. We used methylation-sensitive restriction endonucleases (AciI, BstUI, HpaII, and HinP1I) to assess 5-LOX DNA methylation in brain and heart tissue samples from young (2 months) and old (22 months) mice. We also measured mRNA content for 5-LOX and the DNA methyltransferases DNMT1 and DNMT3a. In young mice, the 5-LOX mRNA content was significantly greater in the heart compared to the brain; 5-LOX DNA methylation was lower, except in the AciI assay in which it was higher in the heart. Aging decreased 5-LOX mRNA content in the heart and increased it in the brain. Aging also increased 5-LOX DNA methylation and this effect was site- (i.e., enzyme) and tissue-specific. Generally, DNMT1 and DNMT3a mRNA content was lower in the brain regions compared to the heart; the only effect of aging was observed in the mRNA content of DNMT3a, which was decreased in the heart of old mice. These results indicate a complex tissue-specific and aging-dependent interplay between the DNA methylation system and 5-LOX mRNA content. Interpretation of this data must take into account that the tissue samples contained a mixture of various cell types.